Inner circles how America changed the world ; a memoir - Haig, Alexander Meigs 1924-2010 (Warner Books, 1992)
To a degree virtually unmatched by any other American of his time, Alexander M. Haig, Jr. has participated in an astounding range of historical events. Among them: the Korean War, Vietnam, the Secret War against Castro's Cuba, Watergate, Nixon's establishment of diplomatic relations with China, the events surrounding the tragic death of John F. Kennedy, and the attempted assassination of Ronald Reagan. Now Alexander Haig, the man who served six U.S. presidents, presents a fiery, fascinating portrait of these events in the order that they occurred in his life, from his post as a young Army staff officer under MacArthur and combat in Korea to his rise inside the White House, to his stormy career as Richard Nixon's last Chief of Staff and his years as a Supreme Commander of NATO. In the process, Haig unravels mysteries and misperceptions of much of recent America and world political history and those who helped make it, from presidents to apparatchiks